A Case of Xanthoma of Bilateral Tendoachilles Reconstructed with Fascia Lata Graft X - S Jaikish; Balaji Sambandam (Journal of Orthopedics and Joint Surgery)
Aims and background: Cerebrotendinous xanthoma is an autosomal recessive disorder characterized by a lack of production of primary bile acids and accumulation of cholestanol in various tissues like the brain, spinal cord, peripheral nerves, eyes, and tendon in the form of xanthomas. This is a case report of one such patient who had xanthoma of both tendoachilles. Case description: A 30-year-old female patient had swelling in both legs. Gradually, it became painful while walking. On examination, she had a swelling of size 10 by 4 cm attached to tendoachilles. Magnetic resonance imaging (MRI) showed features of xanthoma. Staged surgery was done. The mass was fleshy and pale yellow and replaced the entire tendon. The entire mass was removed, creating a defect of about 20 cm. Fascia lata of size 20 by 6 cm was harvested and made into a fourstrand graft. Proximally, it was sutured with fiber wires to the distal part of the muscle. Distally, it was fixed to the calcaneum using a 5 mm suture anchor. Flexor hallucis longus (FHL) tendon was used to augment the reconstruction. At 1 year, she was asymptomatic and gained good strength and ROM in the ankle. Conclusion and clinical significance: Cerebrotendinous xanthoma causes impairment in joint mobility and ambulation. Deposition of cholestanol in the neurons causes atrophy and secondary demyelination. Simple excision of tendoachilles xanthoma will do more harm to the patient who is more prone to neurological and mobility-related issues. Fascia lata graft has the advantage of limited donor site morbidity and adequate length.